Sentence-Level Effects of Literary Genre: Behavioral and Electrophysiological Evidence - Blohm, Stefan; Menninghaus, Winfried; Schlesewsky, Matthias (Frontiers in Psychology, 2017)
The current study used event-related brain potentials (ERPs) and behavioral measures to examine effects of genre awareness on sentence processing and evaluation. We hypothesized that genre awareness modulates effects of genre-typical manipulations. We manipulated instructions between participants, either specifying a genre (poetry) or not (neutral). Sentences contained genre-typical variations of semantic congruency (congruent/incongruent) and morpho-phonological features (archaic/contemporary inflections). Offline ratings of meaningfulness (n=64/group) showed higher average ratings for semantically incongruent sentences in the poetry vs. neutral condition. ERPs during sentence reading (n=24/group; RSVP presentation at a fixed per-constituent rate; probe task) showed a left-lateralized N400-like effect for archaic versus contemporary inflections. Semantic congruency elicited a bilateral posterior N400 effect for incongruent versus congruent continuations followed by a centro-parietal positivity (P600). While N400 amplitudes were insensitive to the genre, the latency of the P600 was delayed by the poetry instruction. From these results, we conclude that, during real-time language comprehension, readers are sensitive to subtle morphological manipulations and the implicit prosodic differences that accompany them. By contrast, genre awareness affects later stages of comprehension.